Pengaruh Ukuran Perusahaan, Profitabilitas, Struktur Modal, Dan Keputusan Investasi Terhadap Nilai Perusahaan (Studi pada Perusahaan Makanan dan Minuman yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2013-2017) - Evi Arnita Sari (Universitas Batanghari Jambi, 2020)
This study consists of independent variables, namely company size, profitability, capital structureand investment decisions and the dependent variable is the value of the company. Formulation of the problem of how to influence the independent variables on the dependent variable simultaneously and partially. In this study the method used is quantitative descriptive method and the analytical tool used is a statistical analysis tool consisting of multiple linear regression models, classical assumption tests (normality, multicollinearity, heterokedacity and autocorrelation), hypothesis testing (f test and t test), and test the coefficient of determination (R2). Based on the results of the study assisted by SPSS 20 devices, the regression equation Y = (-6,435) + 0.775 X1 + 0.002 X2 + (0.009) X3 + 0.001 X4 + e produces the other side simultaneously obtaining the independent variable test significantly influencing the dependent variable. Marked by Fcount> Ftable which is 7.815> 2.46 with a significant level of 0.000 <0.05. And partially only significant company size is indicated by tcount = 0.002 <ttable = 2.03224 meaning that the value of the company size is smaller than the specified level of 0.05. The conclusion obtained by the F test (Simultaneous) is that the independent variable has a significant influence on firm value. While for the t test (partial) only company size has a significant effect on the dependent variable (company value).